1996
DOI: 10.1109/70.544770
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and correction of systematic odometry errors in mobile robots

Abstract: Thi s paper describes a practical method for reducing In a typical differential drive mobile robot incremental odometry errors caused by kinematic imperfections of a mobile encoders are mounted onto the two drive motors to count the robot. These errors, here referred to as "systematic" errors, stay wheel revolutions. After a short sampling interval I the left and almost constant over prolonged periods of time. Performing an right wheel encoders show a pulse increment of N and N , occasional calibration as desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
427
0
10

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 663 publications
(439 citation statements)
references
References 21 publications
2
427
0
10
Order By: Relevance
“…2) was chosen, instead of standard square path (proposed by [8]), to simulate various working conditions of the warehouse platform, such as various turn radii and forward and backward movements. The real orientation angle of the robot was measured optically, in defined stop points along the path, from the picture taken by a camera above the robot.…”
Section: Fig 1 Modified Irobot Roomba Used In the Experimentmentioning
confidence: 99%
“…2) was chosen, instead of standard square path (proposed by [8]), to simulate various working conditions of the warehouse platform, such as various turn radii and forward and backward movements. The real orientation angle of the robot was measured optically, in defined stop points along the path, from the picture taken by a camera above the robot.…”
Section: Fig 1 Modified Irobot Roomba Used In the Experimentmentioning
confidence: 99%
“…The surface, wheels and rollers were cleaned, and the odometry was calibrated before the experiments. The calibration was performed as described in the odometry calibration example from [7], which consists of a simplified version of the Borenstein method [2].…”
Section: Odometrymentioning
confidence: 99%
“…All these defects lead to an unbounded accumulation of the localization error. A proposed solution and study of this type of error can be found in (Borenstein and Feng, 1996;1995;Martinelli, 2001).…”
Section: Introductionmentioning
confidence: 99%